Crime scene investigation : methods and procedures - Pepper, Ian K. (McGraw-Hill Open University Press, 2010)
"The second edition of this book guides aspiring and newly appointed CSIs through the methods and procedures for the accurate recording and recovery of evidence from the scene of a crime."-- Resumé vydavatele
Keywords: kriminalistika; kriminalistika -- Velká Británie; kriminalistická metodika; kriminální případy; criminal investigation; criminal investigation -- Great Britain; criminal investigation methodology; criminal cases; příručky; elektronické knihy; handbooks and manuals; electronic books